VEGFR3 mitigates hypertensive nephropathy by enhancing mitophagy via regulating crotonylation of HSPA1L - Qiuwen Wu; Jiaxin Fu; Bin Zhu; Wei Meng; Jingyi Ma; Ying Lv; Wenqi Zhao; Fan Wang; Jingjin Liu; Yongshun Wang; Cong Peng; Shuo Zhang (Cell Communication and Signaling)
Abstract Oxidative stress-associated proximal tubular cells (PTCs) damage is an important pathogenesis of hypertensive renal injury. We previously reported the protective effect of VEGFR3 in salt-sensitive hypertension. However, the specific mechanism underlying the role of VEGFR3 in kidney during the overactivation of the renin-angiotensin-aldosterone system remains unclear. In the present study, hypertensive nephropathy was established by angiotensin II (Ang II). We found that VEGFR3 was highly increased in PTCs of Ang II-infused mice. Activation of VEGFR3 mitigated renal dysfunction, pathological damage, and oxidative stress in Ang II-induced hypertensive mice. Moreover, we found that VEGFR3 restored mitophagy deficiency induced by Ang II both in vivo and in vitro to alleviate oxidative stress injury in PTCs. Furthermore, in vitro experiment demonstrated that VEGFR3 improved abnormal mitophagy by enhancing PARKIN mitochondrial translocation. LC-MS/MS and Co-IP assays identified HSPA1L as the interacted protein of VEGFR3, which promoted the mitochondrial translocation of PARKIN. Mechanistically, VEGFR3 disorder domain bound to HSPA1L, and crotonylation modification of HSPA1L at K130 by VEGFR3 was required for mitophagy regulation in the context of Ang II-induced PTCs. Finally, the protective effect of VEGFR3 on mitophagy and oxidative stress were attenuated by transfection K130 (HSPA1L-K130R) mutant plasmid in vivo and in vitro. These findings indicated that VEGFR3 alleviated oxidative stress by promoting PARKIN-dependent mitophagy pathway via regulating HSPA1L crotonylation at K130 site in Ang II-induced PTCs, which provided a mechanistic basis for the therapeutic target in hypertensive renal injury.